Analisis Usahatani dan Strategi Pengembangan Kopi Arabika (Coffea Arabica) di Desa Lamba Keli Kabupaten Manggarai Timur - Yohana Angreani; Selfianus (Fakultas Pertanian, Universitas Nusa Nipa, 2024)
The research was conducted from July to August 2023 in Lamba Keli Village, Lamba Leda District. The objectives of this study were (1) to analyze the profits received from Arabica coffee farming, (2) to analyze the efficiency of Arabica coffee farming, and (3) to formulate an appropriate strategy for developing Arabica coffee farming in Lamba Keli Village, Lamba Leda District, East Manggarai Regency. Seventy-nine Arabica coffee farmers were interviewed. The analysis used included revenue, costs, income, business efficiency, and a SWOT analysis. The results showed an average revenue per farmer of IDR 1,107,594, with an average profit of IDR 582,595. The R/C ratio was 2.11. With a profitable farming system, Lamba Keli Village can develop an Arabica coffee strategy. Internal strategic factors that contribute to the strength of Arabica coffee farming include product characteristics, labor, land suitability, and climate. Internal strategic factors that weaken Arabica coffee farming include low technology, limited extension funding, and low production volumes. External strategic factors that provide opportunities for Arabica coffee farming include market demand and business partners. External factors that threaten Arabica coffee farming include changes in consumer tastes, pest and disease attacks, and competition from other commodities. The analysis suggests an alternative strategy: farmers need to collaborate with the village government to support production activities, including additional capital, provision of production facilities with the latest technology, and assistance in cultivating Arabica coffee.